Planning for Universal Child Care: An Evaluation of BC Municipal Child Care Plans - Binet, Andi; Saha, Arunima; Lam, Jake; Al Houseini, Dalia; Espanol, Isabelle; Roberts, Erin (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2025)
In 2018, responding to pressure from local governments and advocacy groups, British Columbia launched a provincial effort to build a universal $10/day child care system. As part of this effort, grants were issued to municipalities to support the development of municipal child care plans. In this paper, we conduct a plan evaluation analysis of 48 child care plans created by B.C. municipalities to characterize this emerging form of planning and understand initial strengths and areas for improvement. Our findings highlight common strategies for child care expansion, as well as areas for improvement in identifying and addressing current inequities. We conclude with lessons for other jurisdictions across Canada where local-level planning will be involved in facilitating child care expansion.